Investigation of the linear and nonlinear optical susceptibilities of KTiOPO4 single crystals: Theory and experiment - Reshak, Ali Hussain; I. V., Kityk; S., Auluck (American Chemical Society, 2011)
Link to publisher's homepage at http://pubs.acs.org/